2006
DOI: 10.1038/sj.onc.1209833
|View full text |Cite
|
Sign up to set email alerts
|

A direct link between expression of urokinase plasminogen activator receptor, growth rate and oncogenic transformation in mouse embryonic fibroblasts

Abstract: In addition to its role in invasion and metastasis of several tumors, the multifunctional urokinase receptor uPAR (urokinase plasminogen activator receptor) is directly involved in the growth of several cancer cells in vitro and in vivo. We have compared growth rate and oncogenic transformation in wild-type (wt) or uPAR À/À mouse embryonic fibroblasts (MEFs). Surprisingly, uPAR À/À MEFs grew faster than wt MEFs. This agreed with elevated levels of cell cycle mediators like extracellular signal-regulated protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
5
1
Order By: Relevance
“…Our findings do not allow us to conclude that expression of M uPAR on HSPCs per se regulates the anchorage-dependent cell cycle, even though M uPAR can regulate the cell cycle (47). Rather, we favor the interpretation that the observed differences in the proliferation status between M uPAR + and M uPAR -HSPCs might be explained, at least in part, by assuming that the M uPAR + HSPC is a different type of progenitor.…”
Section: Bm During Mobilization and Hspc Mobilization Was Impaired Incontrasting
confidence: 37%
“…Our findings do not allow us to conclude that expression of M uPAR on HSPCs per se regulates the anchorage-dependent cell cycle, even though M uPAR can regulate the cell cycle (47). Rather, we favor the interpretation that the observed differences in the proliferation status between M uPAR + and M uPAR -HSPCs might be explained, at least in part, by assuming that the M uPAR + HSPC is a different type of progenitor.…”
Section: Bm During Mobilization and Hspc Mobilization Was Impaired Incontrasting
confidence: 37%
“…Likewise, an 88% inhibition of proliferating cancer cells in colorectal carcinoma in vivo when treated with uPAR monoclonal antibody (ATN658) has been reported recently [67]. In contrast, uPAR overexpression inhibited cell growth in murine embryonic fibroblast cells and induced cell growth in keratinocytes [68]. uPAR has been detected as a potential cooperating oncogene in Ink4a KO mice, which are deficient in cell growth control [69].…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, our c-Src overexpression experiments prove that under specific conditions, the requirement for uPAR in supporting EGF mitogenic activity is eliminated. Mazzieri et al (2006) reported that uPARÀ/À MEFs demonstrate more rapid proliferation and oncogenic transformation, compared with uPAR-positive cells; however, their MEFs were not transformed with SV40 large T antigen. As our MEFs were transformed, the tumor suppressor gene p53 is inactivated (O'Reilly, 1986), as may be observed in human cancers and cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%